2015
DOI: 10.3109/00016489.2015.1107192
|View full text |Cite|
|
Sign up to set email alerts
|

The role of tensor veli platini muscle (TVP) and levetor veli platini muscle (LVP) in the opening and closing of pharyngeal orifice of Eustachian tube

Abstract: Otomiscroscopic, tympanograph, and pathological examination showed the presence of middle ear disease in those animals whose TVP was excised and paralyzed, but on those groups of animals whose LVP was excised and paralyzed, abnormalities were seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…The Eustachian tube (ET) has 3 primary functions pertaining to the middle ear, including ventilation, middle ear clearance, and protection of the middle ear against nasopharyngeal pathogens (Gyanwali et al, 2016). Otitis media with effusion (OME), acute otitis media, cholesteatoma, and atelectasis are some of the pathologic manifestations of deficiency in ET function (Bluestone and Bluestone, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The Eustachian tube (ET) has 3 primary functions pertaining to the middle ear, including ventilation, middle ear clearance, and protection of the middle ear against nasopharyngeal pathogens (Gyanwali et al, 2016). Otitis media with effusion (OME), acute otitis media, cholesteatoma, and atelectasis are some of the pathologic manifestations of deficiency in ET function (Bluestone and Bluestone, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found that secretory otitis media was caused by Eustachian tube dysfunction, with the histopathological changes occurring in the tree shrew like those in humans. 21 In the present study, we irradiated the TVP muscle of tree shrews to develop an animal model to investigate the pathogenesis of radiation-induced muscle injury. The results of this study may serve as a scientific basis for future research and treatment of complications caused by radiation-induced muscle injury.…”
Section: Introductionmentioning
confidence: 99%
“…Estes músculos são os responsáveis por aumentar a luz da tuba auditiva. Diante do comprometimento destes, a tuba auditiva não abre corretamente o que pode favorecer ao acúmulo de fluidos serosos na orelha média (13).…”
Section: Anatomia E Fisiologiaunclassified
“…Dentre os músculos palatinos implicados na MP essencial destacam-se o tensor do véu palatino (TVP) e o levantador do véu palatino (LVP) que possuem inserção na tuba auditiva e desempenham papel importante na mecânica de abertura da mesma (11)(12)(13).…”
Section: Introductionunclassified